THE The Potential Moral of Centennial Women in Building Sakinah Family: Ideality and Reality - Umar Faruq Thohir; Haiyin Lana Lazulfa (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
The Qur'an is the only holy book that talks a lot about the position of women in Islam. Similarly, the religion of Islam greatly glorifies women. In the lens of Islam, women are seen as having a set of potentials that are not possessed by other beings. The existence of women is considered very urgent, especially in the embodiment of the sakinah family. The difference in times will greatly affect the pattern of life and even morals in each woman. Just like centennial women living in this ongoing age of sophistication. The potential to create a good household is also questionable. In the Qur'an it has been alluded to in several verses, especially in Q.S an-Nisa' [4]: 34. The verse will dissect the criteria of an ideal woman in Islam. Through this thematic interpretation search, based on Q.S an-Nisa' [4]: ​​34 it can be understood that the ideal woman who can potentially realize her household in sakinah is a pious woman who is obedient to Allah SWT, and obedient to her husband, and takes care of herself both when she is with her husband and when she is not. Therefore, preparing herself physically and mentally is urgent for centennial women to move towards the household stage.